Buletin Peternakan : ESTIMASI HERITABILITAS SIFAT PERTUMBUHAN DOMBA EKOR GEMUK DI UNIT PELAKSANA TEKNIS PEMBIBITAN TERNAK-HIJAUAN MAKANAN TERNAK GARAHAN - Sumadi, Jatmika Prajayastanda, Nono Ngadiyono (Peternakan UGM, 2014)
Sheep is one of popular ruminants in Indonesia, because sheep is one one of source of animal protein, and also easy and convenient in breeding. Therefor, they should be developed, preserved and increased through improvement of genetic quality by selection and mating control in the breeding program.